Effect of climate change on potential distribution of Cedrus libani A. Rich in the twenty-first century: an Ecological Niche Modeling assessment - López-Tirado, Javier; Vessella, Federico; Stephan, Jean; Ayan, Sezgin; Schirone, Bartolomeo; Hidalgo, Pablo J. (Springer Science and Business Media LLC, 2020)
The present study is focused on the potential distribution of the Lebanese cedar (Cedrus libani) in the present and in the future throughout the twenty-first century. The location of this work encompasses Lebanon, Syria and Turkey. Twenty-four environmental variables are used and two Representative Concentration Pathways (RCP) scenarios for two different time periods are studied: RCP 4.5 2050, RCP 4.5 2070, RCP 8.5 2050 and RCP 8.5 2070. The most interesting novelty is the use of 13 General Circulation Models and 6 algorithms (Climate Space Model, Envelope Score, Environmental Distance, Genetic Algorithm for Rule-set Production, Maximum Entropy and Support Vector Machines) were considered for modelling. Area Under the Curve is used as goodness of fit and building the final consensus map. The global habitat suitability area would enlarge in the forecasted scenarios with respect to the present, although it would be more restricted in 2070 due to the altitudinal shift. This study also suggests an interesting approach to manage C. libani stands by means of afforestation programs aiming to face global warming in the late twenty-first century.
Keywords: Near East; Cedrus libani; Ecological Niche Modeling; Potential distribution; Climate change; Forecasting; 13. Climate action; 15. Life on land